2021
DOI: 10.1111/1471-0307.12798
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of amino acid, mineral and vitamin profiles of milk from Turkish Saanen, Hair and Maltese goat breeds throughout lactation

Abstract: This study aimed to evaluate the changes in nutritional compounds such as amino acids, minerals, and vitamins in the milk of Turkish Saanen, Hair and Maltese goat breeds. The Turkish Saanen goat breed had lower dry matter, fat, nitrogen, and vitamins A, E and B 2 than Maltese and Hair goat breeds throughout lactation period. High levels of proline, leucine, glutamic acid, and glutamine were found in all breeds. Except for tyrosine, all other amino acids were higher in Hair goat milk than those in other breed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…Meanwhile, Sramek et al [ 15 ] found a non-significant increase in proteins, a significant increase in milk fat, and a significant decrease in lactose content in the high SCC group (>1000 × 10 3 cell/mL) milk of Alpine goats. The reduction in lactose concentration can be a result of increased plasmin activity; the higher content of total protein can be related to the increase in albumin and whey protein concentrations in milk during subclinical or clinical mastitis [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, Sramek et al [ 15 ] found a non-significant increase in proteins, a significant increase in milk fat, and a significant decrease in lactose content in the high SCC group (>1000 × 10 3 cell/mL) milk of Alpine goats. The reduction in lactose concentration can be a result of increased plasmin activity; the higher content of total protein can be related to the increase in albumin and whey protein concentrations in milk during subclinical or clinical mastitis [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other studies showed that high levels of Pro, Leu, and Glu + Gln were determined in goat milk from Saanen and Alpine goat breeds, while His and Tyr were found to be at a lower level than the other amino acids determined in goat milk samples. It was found that the contents of Pro, Leu, and Glu + Gln were in the range of 25.49–50.14, 24.53–35.79, and 21.34–35.28 µmol/mL, respectively, while the contents of His and Tyr were found to be in the range of 3.70–5.36 and 3.31–5.67 µmol/mL, respectively [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Goat milk has high nutritional value, therapeutic and dietary characteristics, in addition to high digestibility (Haenlein, 2004). Goat milk contains a high level of short-and mediumchain fatty acids with a small size of fat globules (~2.5-3 μm in diameter), while it has a low level of αs1-casein (4.5%-34% of the total protein) and a high level of β-casein (34%-64% of the total protein) (Günay et al, 2021). Moreover, goat milk also has whey proteins (WPs) at a level of 3-12 g/kg.…”
Section: Introductionmentioning
confidence: 99%
“…The natural and healthy image and specific taste of goat milk make goat dairy products a profitable alternative (Fangmeier et al, 2019). This is because goat's milk is known for its beneficial and therapeutic effects on people who are allergic to cow's milk which, combined with nutritional and health benefits, strengthen the potential and value of goat milk and its derivatives (Popović-Vranješ et al, 2017;El-Shafei et al, 2020;Hadjimbei et al, 2020;Günay et al, 2021).…”
Section: Introductionmentioning
confidence: 99%